KERAGAMAN KOMPOSISI JENIS DAN STRUKTUR VEGETASI PADA KAWASAN HUTAN LINDUNG DENGAN POLA PHBM DI BKPH TAMPOMAS, KPH SUMEDANG, PERUM PERHUTANI DIVISI REGIONAL JAWA BARAT DAN BANTEN Species Composition and Vegetation Structure of Protected Forest Area using . - Cecep Kusmana; Anggun Rahayu Melyanti (Jurnal Silvikultur Tropika, 2017)
BKPH Tampomas is part of the FMU area of Sumedang entirely classified into protected forest area. However, part of treated as CBFM with the aim of involfing the community in forest concervation activities the aim of this research is to describe and compare the structure and composition of the plant species between the subjected to CBFM and non CBFM Tampomas. The reaserch location was based on forest status of the protected area as having the same stand age and tree spacing. Data collection conducted throught the analysis of vegetation and soil sampling at each observation location species richness of BKPH Tampomas protection forest was relatively low either non CBFM of protected forest, CBFM protection forest of coffe and CBFM protection forest of cardamon. At the level of seedling stage there are 9 species and Calliandra haematocephala, the dominant. Species at the pole stage are found 3 species with Pinus merkusii species as the dominant species, at the tree stage are 2 species that dominated by Pinus merkusii. The covercrop found were 30 species and dominated by Lepturus repens. The low soil fertility and sandy soil texture composition also account for the low plant species in the BKPH Tampomas protection forest areas.Key words : CBFM cardamon, CDFM coffee, species composition, structure vegetation, Tampomas Mountain